Study investigating the role of skeletal muscle mass estimation in metastatic spinal cord compression - Gakhar, H.; Dhillon, Amandeep Kaur; Blackwell, J.; Hussain, K.; Bommireddy, R.; Klezl, Z.; Williams, John P. (Springer Verlag, 2015)
Background